2020
DOI: 10.37187/gjoes.0620.0202.02
|View full text |Cite
|
Sign up to set email alerts
|

Sample Size Measurement

Abstract: Knowing exact sample size for a population for quantitative study is one of the most important tasks, which needs to be properly addressed, before starting data collection for research. Multiple factors are involved in determining a sample size i.e. population size, degree of freedom, desired significance level and desired level of precision. We provide a table to find a suitable sample size for any given population, on the basis of sampling formula given by Cochran (1953), with the sole purpose of making samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many researches also support the rule of thumb that for each construct there must be at least 10 observations. Depending upon the size of the target population (students enrolled in the universities) and taking 95% confidence interval, the minimum sample required for the study came out to be 384 using a sampling formula [ 59 ]. Thus, our sample size meets all the above criteria for a representative sample.…”
Section: Methodsmentioning
confidence: 99%
“…Many researches also support the rule of thumb that for each construct there must be at least 10 observations. Depending upon the size of the target population (students enrolled in the universities) and taking 95% confidence interval, the minimum sample required for the study came out to be 384 using a sampling formula [ 59 ]. Thus, our sample size meets all the above criteria for a representative sample.…”
Section: Methodsmentioning
confidence: 99%
“…Kamakia et al (2017) identified a positive association between FL and FW. Younas et al (2019) poise that an improvement in FL would result in enhanced FW. Rahman et al (2021) also affirmed that FL is very relevant when predicting FW.…”
Section: Developing Hypotheses Based On Empirical Evidencementioning
confidence: 99%